Assessing the on-farm effects of removing salts from irrigation water - Shrestha, Sanskriti, author; Bailey, Ryan, advisor; Sharvelle, Sybil, committee member; Butters, Gregory, committee member (Colorado State University. Libraries, 2023)
In dry and semi-arid places where precipitation is insufficient to sustain a regular percolation of water through the soil, salt-induced land degradation is frequent. Desalination of irrigation water is an emerging alternative that can be utilized to repurpose our salt-affected agricultural lands, thus providing an avenue for sustaining the growing production demands with limited water and land resources. Therefore, a combination of fieldwork, modeling and soil sensor records was implemented to evaluate the feasibility of an on-farm Reverse Osmosis (RO) system, in terms of crop yield and soil salinity, for the desalination of irrigation water over three growing periods. Four types of treatment systems were applied to 16 experimental field plots at the Arkansas Valley Research Center (Rocky Ford, CO), representing soil conditions of the Lower Arkansas River Valley (LARV), a region of which approximately 70% is affected by salt-induced crop yield loss. Statistical t-tests done on the data of the three seasons did not show any significant differences in the VMC, EC and biomass of the plots irrigated with the different treatments. Results of the tests for season 3, which showed an increase in t-values and a decrease in p-values demonstrated the need for a longer study period to gauge any significant effects. Similarly, the results of sensor data did not show a significant decrease in soil salinity for the study period. The average soil electrical conductivity (EC) showed a 20% to 26% reduction in soil salt mass in the fields irrigated with desalinated water over the three seasons, however, the EC results did not show a consistent decreasing trend across the 16 plots. A 6-year numerical modeling forecast done by the hydro-chemical model HYDRUS 1D simulating dry, average, and wet weather showed a 6% to 20% reduction in EC when desalination was applied to the fields. These preliminary results of the field and modeling approaches provide encouragement for the continuation of desalination treatments to see any substantial long-term effects.
Keywords: on-farm desalination; salinity; HYDRUS 1D; UNSATCHEM; RO desalination